Stumpage Appraisal for Timber Concessions in Lao People's Democratic Republic - Akkharath, Inthavy (1997)
Forest lands in Lao People's Democratic Republic (Lao PDR) are largely owned and administered by the government. The government allocates forest logging areas to private companies through long-term contracts which defines the rights and other duties of the concessionaires to extract logs from the forest. Concessionaires have to pay timber fee to the provincial government under the agreement for rights to extract the logs. The timber fee collected by the government is the royalty rate, assessed on volume timber extracted and differentiated by species. The royalty collected does not reflect the appropriate stumpage value concessions, most obvious is the loss in revenue which reduces the apparent viability of government investment in forest management. This study was conducted to estimate stumpage values of various compartments and their capture by the government and concessionaires for three logging concessions in Lao PDR.